The architecture of the Sudanese agricultural sector and its contribution to the economy between 1990 and 2021 - Alhelo, Alzaki; Siddig, Khalid; Kirui, Oliver K. (International Food Policy Research Institute, 2023)
The paper reviews the performance of the Sudanese agricultural sector over the last three decades (1990 through 2021) and examines the drivers of that performance. Key findings show that the sector’s contribution to gross domestic product was greater during the 1990–1999 period than during the other two decades; agricultural productivity as well was higher in that decade than in the subsequent two decades. The sector has remained a major source of employment and livelihood. During the last decade reviewed (2010–2021), the sector regained its leading position as a generator of foreign currency. Public investment in agriculture and government spending allocated to the sector were lower than in other countries in the region. Political elites have generally lacked commitment to development plans in the sector. Political developments in Sudan have disrupted more recent efforts to revitalize the sector. Climate change, as manifested in rising temperature, declining rainfall, and drought, is a substantial determinant currently affecting the sector. The paper discusses some broad recommendations for improving the performance of the Sudanese agricultural sector.